STUDY OF THE MINERALOGICAL COMPOSITION OF THE COAGULANT-ADSORBENT APAK - Aymurzaeva, L.G.; Aytbaeva, H.B.; Zaripbayev, K.Sh. (SCIENCE and SOCIETY, 2026)
This article presents data on the study of the mineralogical composition of the coagulant-adsorbent obtained on the basis of Angren kaolin and natural mirabilite. Thermochemical activation revealed changes in the mineralogical composition and structure of minerals with increasing temperature. The coagulant-adsorbent obtained by thermochemical activation at temperatures of 600°C÷650°C was studied by X-ray phase analysis of samples of primary variegated Angren kaolin, mirabilite, and based on them from the Jaslyk deposit of the Republic of Karakalpakstan.
Keywords: Angren kaolin; natural mirabilite; kaolinite minerals; radiograph; coagulant-adsorbent; thermochemical activation; diffraction maximum